Immunization With the CSF-470 Vaccine Plus BCG and rhGM-CSF Induced in a Cutaneous Melanoma Patient a TCRβ Repertoire Found at Vaccination Site and Tumor Infiltrating Lymphocytes That Persisted in Blood - Aris, Mariana; Bravo, Alicia Inés; Garcia Alvarez, Heli Magalí; Carri, Ibel; Podaza, Enrique; Blanco, Paula Alejandra; Rotondaro, Cecilia; Bentivegna, Sofia; Nielsen, Morten; Barrio, María Marcela; Mordoh, José (Frontiers in Immunology, 2019)
The CSF-470 cellular vaccine plus BCG and rhGM-CSF increased distant metastases-free survival in cutaneous melanoma patients stages IIB-IIC-III relative to medium dose IFN-α2b (CASVAC-0401 study). Patient-045 developed a mature vaccination site (VAC-SITE) and a regional cutaneous metastasis (C-MTS), which were excised during the protocol, remaining disease-free 36 months from vaccination start. CDR3-TCRβ repertoire sequencing in PBMC and tissue samples, along with skin-DTH score and IFN-G ELISPOT assay, were performed to analyze the T-cell immune response dynamics throughout the immunization protocol. Histopathological analysis of the VAC-SITE revealed a highly-inflamed granulomatous structure encircled by CD11c+nested-clusters, brisk CD8+ and scarce FOXP3+ lymphocytes with numerous Langhans multinucleated-giant-cells and macrophages. A large tumor-regression area fulfilled the C-MTS with brisk lymphocyte infiltration, mainly composed of CD8+PD1+ T-cells, CD20+ B-cells and scarce FOXP3+ cells. Increasing DTH score and IFN-γ ELISPOT assay signal against the CSF-470 vaccine-lysate was evidenced throughout immunization. TCRB repertoire analysis revealed for the first time the presence of common clonotypes between a VAC-SITE and a C-MTS; most of them persisted in blood by the end of the immunization protocol. In vitro boost with the vaccine-lysate revealed expansion of persistent clones that infiltrated the VAC-SITE and/or the C-MTS; other persistent clones expanded in the patient’s blood as well. We propose that expansion of such persistent clonotypes might derive from two different although complementary mechanisms: proliferation of specific clones as well as expansion of redundant clones, which increased the number of nucleotide rearrangements per clonotype, suggesting a functional antigenic selection. In this patient, immunization with the CSF-470 vaccine plus BCG and rhGM-CSF induced a T-cell repertoire at the VAC-SITE that was able to infiltrate an emerging C-MTS, which resulted in the expansion of a T-cell repertoire that persisted in blood by the end of the 2-year treatment.